Conciliation études-travail rémunéré : cas des adolescent.e.s et jeunes de la commune de Tchaourou au Bénin - Judicaël Alladatin; Ronel Akakpo; Anselme Houéssigbédé (Presses universitaires de la Méditerranée, 2018)
This study is about conciliation of study and gainful work among teenagers and young people in the area of Tchaourou in Benin. It aims to identify the personal and family characteristics of teenagers and youth aged 12 to 24 who are studying while pursuing an income-generating activity. Our results reveal that 20.71 % of teenagers and young people surveyed conciliate study and gainful work. Mens are most affected than women, and the frequency of paid-labor and study increases with age. The study highlights the role of the theory of crisis in explaining of conciliation of study and gainful work among teenagers and young people. Indeed, teenagers and young who have insufficient financial support and those living in poor households are most affected for the conciliation of studies and paid work.